2020
DOI: 10.1101/2020.10.12.332569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM reveals structural breaks in a patient-derived amyloid fibril from systemic AL amyloidosis

Abstract: Systemic AL amyloidosis is a debilitating and potentially fatal disease that arises from the misfolding and fibrillation of immunoglobulin light chains (LCs). The disease is patient-specific with essentially each patient possessing a unique LC sequence. In this study, we present the first ex vivo fibril structures of a λ3 LC. The fibrils were extracted from the explanted heart of a patient (FOR005) and consist of 115 residues, mainly from the LC variable domain. The fibril structures imply that a 180° rotation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Several recent studies report structural differences between fibrils formed inside a test tube and fibrils extracted from diseased tissue [4][5][6][7][8] . Morphological differences depend, on the one hand, on the primary structure of the aggregating polypeptide chain and on the other hand on the conditions under which fibril formation occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies report structural differences between fibrils formed inside a test tube and fibrils extracted from diseased tissue [4][5][6][7][8] . Morphological differences depend, on the one hand, on the primary structure of the aggregating polypeptide chain and on the other hand on the conditions under which fibril formation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro fibrils reproduce the generic structural features of amyloid fibrils, such as their linear morphology, cross-β structure and affinity for Congo red and thioflavin T dyes 3 , but an increasing number of recent studies found fibrils from patient tissue to be structurally different from in vitro fibrils from the same precursor protein. Examples hereof are the immunoglobulin light chain-derived fibrils in systemic AL amyloidosis 4,5 , the Aβ-derived fibrils in Alzheimer's disease 6 , tauderived fibrils in neurodegenerative diseases 7 , or the α-synucleinderived fibrils in multiple system atrophy 8 . Hence, out of the spectrum of fibril morphologies, that a polypeptide chain is able to adopt, only some morphologies are associated with disease, raising the question what might determine their pathological relevance?…”
mentioning
confidence: 99%
“…Due to sensitivity issues, we were not able so far to collect a greater number of longrange distance restraints using e.g. PAR or PAIN type experiments (52,53). Very recently, the ALfibril structure obtained from patient tissue has been solved using cryo-EM (54).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the proteolytic fragmentation that leads to loss of the variable domain is not fully understood, but proteomic experiments indicate that at least some cleavage occurs after deposition as amyloid (Lavatelli et al, 2020;Mazzini et al, 2022). High resolution structures of amyloid fibrils show that their cross-β core is formed from variable domain residues in nonnative conformations, with the disulfide bond intact but the orientation of the peptide chains around the disulfide reversed, relative to that in the native state (Radamaker et al, 2019(Radamaker et al, , 2021a(Radamaker et al, , 2021bSwuec et al, 2019). Unfolding of the native light chains is therefore required for amyloid formation.…”
Section: Introductionmentioning
confidence: 99%